Kaempferol ameliorates secretagogue‐induced pseudo‐allergic reactions via inhibiting intracellular calcium fluctuation. (18th June 2020) - Cao, Jiao; Wang, Yuejin; Hu, Shiling; Ding, Yuanyuan; Jia, Qianqian; Zhu, Jing; An, Hongli
Abstract: Objectives: To investigate the inhibitory effects of Kaempferol, a natural flavonol active compound, on pseudo‐allergic reactions ( in vivo and in vitro ), particularly on the mechanism underlying its effect in human mast cells. Methods: Compound 48/80 (C48/80)‐induced immunoglobulin E (IgE)‐independent passive cutaneous anaphylaxis (PCA) model and systemic anaphylaxis were applied to investigate the anti‐allergic activity of Kaempferol. The degranulation assay, calcium imaging and the secretion of cytokines and chemokines were used to evaluate the inhibitory effect on mast cell activation. Western blot analysis was performed to investigate intracellular calcium fluctuation‐related signalling pathways. Key findings: Kaempferol dose‐dependently attenuated C48/80‐induced mice hind paw swelling, dye extravasation and skin mast cell degranulation, and rehabilitated the hypothermia, as well as reduced the serum concentrations of histamine, tryptase, tumour necrosis factor‐alpha (TNF‐α), interleukin‐8 (IL‐8) and monocyte chemo‐attractant protein‐1 (MCP‐1). Furthermore, Kaempferol suppressed C48/80‐triggered human MC degranulation and calcium fluctuations by inhibiting phospholipase Cγ (PLCγ) phosphorylation and subsequent cytokines synthesis pathways. Conclusions: The inhibition of the process of PLCγ phosphorylation to Ca 2+ mobilization represents a major strategy in Kaempferol‐suppressed pseudo‐allergic reactions. Thus, Kaempferol could be considered as a therapeutic drug candidate for non‐IgE‐mediated allergic reactions or inflammations.